2017
DOI: 10.3748/wjg.v23.i1.167
|View full text |Cite
|
Sign up to set email alerts
|

Ileo-ileal intussusception caused by lymphangioma of the small bowel treated by single-incision laparoscopic-assisted ileal resection

Abstract: Intraabdominal lymphangiomas are uncommon; additionally, those affecting the gastrointestinal tract are rare and account for less than 1% of cases. Intussusception caused by a cystic lymphangioma of the small bowel is extremely rare. The patient was a 20-year-old woman who visited our emergency room with a complaint of abdominal pain. A computed tomography image revealed ileo-ileal intussusception with a leading hypovascular mass measuring 1 cm in a diameter. Single-incision laparoscopic-assisted ileal resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…To our knowledge and with literature review there has been one more case reported of ileo-ileal intussusception has occurred due to lymphangioma in an adult [7] . The definitive treatment for gastrointestinal cystic lymphangioma is resection, with resection of the involved segment of bowel the most preferred procedure.…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge and with literature review there has been one more case reported of ileo-ileal intussusception has occurred due to lymphangioma in an adult [7] . The definitive treatment for gastrointestinal cystic lymphangioma is resection, with resection of the involved segment of bowel the most preferred procedure.…”
Section: Discussionmentioning
confidence: 90%
“…There have been several case reports on the patients with small intestinal lymphangioma causing intussusception in adults [ 1 , 3 , 4 , 6 ]. In all these reports, the patients presented with abdominal pain with or without nausea.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphangiomas are benign tumors resulting from congenital lymphatic system malformation [ 3 ], generally located in the head and neck regions or the axilla. The gastrointestinal lymphangioma accounts for only 1% of all [ 4 , 5 ]. Small bowel lymphangioma causing intussusception is rare, there have only been a few reports published [ 1 , 3 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been evidence that ADPKD predisposes to renal cancer, there is new evidence that it could predispose to other types of cancer, specifically along the GI tract or in the liver [ [9] , [10] , [11] , [12] ]. Gene mutations could predispose individuals to tumor formation, through signaling pathway disruptions, specifically suppression of the apoptotic pathway [ 3 , 11 , 13 , 14 ]. The signaling derangements, specifically signaling inhibitors, found in ADPKD and solid tumors are strikingly similar [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphangiomas are benign tumors comprised of congenitally dilated lymphatic channels and occur most often in the axilla, head and neck [ [1] , [2] , [3] ]. Lymphangioma of the GI tract comprises only 1% of lymphangioma diagnoses, but with increased utilization of endoscopic procedures the incidental discovery of these tumors in GI tract is increasing, leading us to believe the are more common than previously reported [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%